1957
DOI: 10.1002/path.1700740220
|View full text |Cite
|
Sign up to set email alerts
|

Primary melanoma of the meninges

Abstract: THE melanomas that originate in the meninges bear a general structural resemblance to those arising elsewhere, but it is questionable whether they ever metastasise outside the central nervous system. With rare exceptions, however, they have proved fatal. Most cases have clearly been tumours infiltrating t,he brain massively, but in some there was no destruction of brain substance at all, and an attempt is made in this paper to discover whether a benign form of the condition exists. The published case material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

1962
1962
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…In the previous report, the incidences of brain and spinal cord melanoma by age showed a peak in the third decade. In this paper, 21 cases (male 12, female 4, unknown 5) were described and the median age was 25.4 years old and the age distribution was as follows : Gibson et al (1957) reported that the 4th decade was most frequent in the Western countries. Takeda et al (1974) reported that the diffuse black pigmentation was seen in meninges encephali in 42 out of 43 cases in Japan, and in 14 cases among them a deposit was observed in hemisphaerium.…”
Section: Numbers Of Malignant Melanoma Between 1961 and 1976mentioning
confidence: 99%
“…In the previous report, the incidences of brain and spinal cord melanoma by age showed a peak in the third decade. In this paper, 21 cases (male 12, female 4, unknown 5) were described and the median age was 25.4 years old and the age distribution was as follows : Gibson et al (1957) reported that the 4th decade was most frequent in the Western countries. Takeda et al (1974) reported that the diffuse black pigmentation was seen in meninges encephali in 42 out of 43 cases in Japan, and in 14 cases among them a deposit was observed in hemisphaerium.…”
Section: Numbers Of Malignant Melanoma Between 1961 and 1976mentioning
confidence: 99%
“…Age at presentation has ranged from 20–77 years with a mean age of 49.1 years. Past reports have suggested that a younger age at diagnosis (<50 years old) may distinguish primary CNS melanomas from cutaneous melanoma metastases [3, 7]. However, pineal melanomas do not appear to peak in incidence as early in life as other primary CNS melanomas (30s versus 40s) [3].…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 out of 6 cases of primary pineal malignant melanoma with documented skin exams found skin lesions. In both cases, the lesions were found to be benign on histology [3, 6,9,10,11,12]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations